Tratamento de efluente de piscicultura orgânica utilizando macrófitas aquáticas Eichhornia crassipes (mart. Solms) e Egeria densa (Planchon.) - Gentelini, André Luis (2007)
The objective of the recent research was to evaluate the efficiency of a system of aquatic treatment being used macrophytes Eichhornia crassipes (water hyacinth) and Egeria dense (egeria) in three times of hydraulic detention, the removal of pollutants of the effluent one of organic culture of tilápias of the Nile (Oreochromis niloticus), and to get given of production of biomass of the aquatics macrophytes. The work was carried through in the Paturi farm, Terra Roxa city, state of the Paraná, during the period of 6 weeks. The system was composed for 18 experimental tanks of 2.00 x 1.00 x 0.65m length, width and depth respectively, coated with polypropylene canvas. An entirely randomized 2 macrophytes x 3 hydraulic detention times (HDT) and 3 repetitions. The used HDT had been of 04h, outflow of ≈ 4.15 L.min-1, 08h, outflow of ≈ 2.10 L.min-1 and 12h, outflow of ≈ 1.40 L.min-1. The samples were collected in inlet and outlet of the system, in intervals of five days, being evaluated total nitrogen (NT), total phosphorus (PT), ammonia, nitrite, nitrate, turbidity, DQO, pH and electric conductivity. The temperature was measures daily. The biomass production was evaluated to the end of the experiment. For NT in such a way the water hyacinth and would egeria as it biggest removal (P<0.05) 39.90% and 37.38%, respectively was observed in the HDT of 12 hours, not differing from the HDT of 8 hours. The best removals of PT (P<0.05) 41.57% and 43.42% had been observed in the HDT of 12 hours for the water hyacinth and would egeria respectively. In the case of the turbidez, biggest removal 62.74% (P<0.05) was observed in the HDT of 12 hours for the water hyacinth, not differing from the HDT of 8 hours, already for it would egeria optimum resulted (P<0.05) was observed in the HDT of 12 hours with 81.81%. For the DQO, as much the water hyacinth as it would egeria it, the best ones resulted of removal (P<0.05) 63.61% and 62.64% had been observed in the HDT of 12 not differing from the HDT of 8 hours. For the biomass production the water hyacinth presented the best ones resulted, being greater 8.95 kg.m-2 for the HDT of 4 hours, followed for the HDT of 12 and 8 hours, already for would egeria optimum 0.05kg.m-2 in the HDT of 12 hours result, followed for the HDT of 8 and 4 hours. One concludes that for removal of NT, PT, turbidez and DQO the TDH of 12 hours was what it presented better resulted for both the macrophytes. The water hyacinth produced more biomass that egeria in these conditions in all the TDH.